Temporary Jobs, Employ Protection and Labor Market Performance - Fabien Postel-Vinay; Pierre Cahuc (Institute for the Study of Labor (IZA), 2001)
Many European labor markets are characterized by heavy employment protection taxes and the widespread use of fixed-duration contracts. The simultaneous use of these two policy instruments seems somewhat contradictory since the former primarily aims at limiting job destruction whereas the latter clearly intensifies it. In this paper, we use a simple matching model with endogenous job destructions to analyze the impact of a combination of the two policies. We find that the political support of insiders to firing restrictions does not necessarily worsen unemployment. In fact, it may be the willingness of a majority of workers to support the combination of two instruments with opposite effects on job destruction and job creation that increase unemployment and deteriorates efficiency. Moreover, we argue, that the concentration of firm ownership is likely to influence labor market regulations. We show that the preferred point of a majority of workers is a very flexible labor market, without any firing cost when profits are evenly distributed across the labor force (which portrays a situation where firm ownership is extremely dispersed), whereas a combination of job protection and temporary jobs is preferred by workers when the share of profits that they earn is zero (which corresponds to a situation where firm ownership is concentrated among a few shareholders not participating in the labor market).
Keywords: J41; J38; J23; H29; J64; 330; Unemployment; fixed duration contracts; job destruction; employment protection; Theorie der Arbeitslosigkeit; Arbeitsrecht; Kündigungsschutz; Befristeter Arbeitsvertrag; Beschäftigungseffekt; Wohlfahrtseffekt; Public Choice; Eigentümerstruktur; Theorie